2012
DOI: 10.1159/000341239
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Fournier® Cervical Specimen Self-Sampling Device Using the Papanicolaou Method

Abstract: Introduction: Communities of socially excluded immigrant women, especially Muslim, Asian, Aboriginal and Maroon, are among the groups of women with low rates of cervical screening. Exclusion of the pelvic examination could result in a higher acceptance of the cervical screening among these communities and an increase in screening coverage. Aim: To assess the performance of the Fournier® cervical specimen self-sampling device for the cytological diagnosis of precursor or neoplastic lesions in the uterine cervix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The curtailed validity of cytology versus HPV, however, should not lead us to ignore the possibilities of reflex cytology in self-sampling. The sensitivity and the specificity of our self-collected smears show very similar figures to those of other works with the same gold standard 15,27 , allowing us to avoid visits only for Pap smear collection, whenever the self-sample resulted in a smear with non-reactive atypia or dysplasia 24,25 . During our inquiries about the validity of the scrutinized tests, we observed a much higher ratio of unsatisfactory smears among specimens taken by the gynaecologists than by the women.…”
Section: Discussionsupporting
confidence: 73%
“…The curtailed validity of cytology versus HPV, however, should not lead us to ignore the possibilities of reflex cytology in self-sampling. The sensitivity and the specificity of our self-collected smears show very similar figures to those of other works with the same gold standard 15,27 , allowing us to avoid visits only for Pap smear collection, whenever the self-sample resulted in a smear with non-reactive atypia or dysplasia 24,25 . During our inquiries about the validity of the scrutinized tests, we observed a much higher ratio of unsatisfactory smears among specimens taken by the gynaecologists than by the women.…”
Section: Discussionsupporting
confidence: 73%
“…153 Few studies have compared the accuracy of cytology between self-samples and clinician-collected samples using different types of self-sample devices, demonstrating fair-moderate agreement and lower sensitivity on self-collected samples. [153][154][155][156][157][158] In one of the earliest studies of self-collected Pap tests, 154 sensitivity for self-collected cytology using a traditional cytobrush was significantly lower than clinician-sampled cytology (55% vs 85%); however, specificity for self-collected samples was higher (85% vs 73%). Since that time, a variety of self-collection methods and commercial and noncommercial devices have been investigated, with varying results.…”
Section: Self-sampling Beyond Hpv Testing Cytologymentioning
confidence: 99%
“…Previous studies have examined the sensitivity and predictive value of HPV detection by comparing self-collected and clinician collected samples for HPV testing (Cerigo et al, 2012;da Silva Rocha et al, 2012). Studies have shown that self-sampling yields more often HPV-positive results compared to physician-collected samples (Cerigo et al, 2012).…”
Section: Advantages and Limitations Of Self-samplingmentioning
confidence: 99%